Microbial and Physico-Chemical Characterization of Cold Smoked Sea Bass (Dicentrarchus labrax), a New Product of Fishery - Michela Pellegrini; Lucilla Iacumin; Jelka Pleadin; Greta Krešić; Elisabetta Orecchia; Andrea Colautti; Ana Vulić; Nina Kudumija; Cristian Bernardi; Giuseppe Comi (Foods, 2023)
The aim of this study was to investigate the microbial and physico-chemical characteristics of cold smoked sea bass (CSSB), a novel italian fish product. The microbiological analyses showed the presence of bacterial contamination from the raw material, the environment, and the production process. The microbial spoilage population was dominated by lactic acid bacteria (LAB) associated with Gram-negative fermenting bacteria, including Photobacterium phosphoreum and psychrotrophic Enterobacteriaceae. Brochotrix thermospacta and Aeromonas spp. were also present; in contrast, mould and yeast were not detected (<2 CFU/g). High levels (6–7 log CFU/g) of LAB and total bacteria count (TBC) were observed from day 45 of storage; however, their presence does not seem to have influenced the total volatile basic nitrogen (TVB-N), which always remained below 35 mg N/100 g. Consequently, the product is acceptable until day 60 of storage, considering that the malonaldehyde index (TBARS) was lower than 6.5 nmol/g. Pathogenic bacteria such as Salmonella spp. and Listeria monocytogenes were not detected. Currently, there is a growing demand for seafood due to its high quality and nutritional value. Cold smoked sea bass offers a source of macro- and micronutrients essential for the proper functioning of the human body. It is also rich in protein and omega-3 fatty acids. The WHO and FAO evaluated the benefits and risks and concluded that there is convincing evidence of health benefits from fish consumption, such as a reduction in the risk of heart failure and improved neurodevelopment in infants and young children when fish is consumed by the mother before and during pregnancy. The CSSB analysed in this study demonstrated to have health benefits due to long-chain omega-3 PUFAs and other nutrients, such as proteins, minerals, and vitamin D, which are sometimes difficult to obtain from other sources. The results show that CSSB has a high nutritional value and excellent microbial quality.